Upaya penurunan jumlah kematian ibu dan bayi melalui peran stakeholder - jonni sitorus (Inovasi, 2020)
The number of maternal deaths in North Sumatra in 2017 was recorded in Labuhanbatu Regency and Deli Serdang Regency as many as 15 deaths, Langkat Regency with 13 deaths, and Batubara Regency with 11 deaths. Efforts to accelerate the reduction of Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are carried out to ensure that every mother is able to access quality maternal health services, such as maternal health services, delivery assistance by trained health personnel in health care facilities, postpartum care for mothers and babies, special care and referrals if complications occur, the ease of obtaining maternity and childbirth leave and family planning services. Efforts to reduce MMR and IMR are not only the responsibility of one sector, but need the involvement and roles of other stakeholders to accelerate the reduction of MMR/IMR. This study aims to provide recommendations for the reduction of MMR/IMR through the role of stakeholders in North Sumatra. The study used a qualitative method with a phenomenological approach which was conducted from May to September 2019. The research locations were: Mandailing Natal Regency, Deli Serdang Regency, Simalungun Regency, and Sibolga City. The research subjects consisted of 3 (three) elements, namely: Government, Private and Community. Data collection was carried out through observation and through Focus Group Discussion (FGD). This study concludes that the model of efforts to reduce maternal and infant mortality rates must be carried out in a holistic and integrative manner with medical, social, and cultural approaches, starting from health services for adolescent girls, women of productive age, pregnant women, maternity, newborns and toddlers. Efforts to reduce MMR and IMR are the responsibility of all DPOs and elements of academia, business and community, whose programs and activities are integrated. Efforts to reduce MMR and IMR must be viewed from various perspectives, including from a medical, social and cultural perspective.